2(-x-5)=-3x-7

Simple and best practice solution for 2(-x-5)=-3x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-x-5)=-3x-7 equation:


Simplifying
2(-1x + -5) = -3x + -7

Reorder the terms:
2(-5 + -1x) = -3x + -7
(-5 * 2 + -1x * 2) = -3x + -7
(-10 + -2x) = -3x + -7

Reorder the terms:
-10 + -2x = -7 + -3x

Solving
-10 + -2x = -7 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-10 + -2x + 3x = -7 + -3x + 3x

Combine like terms: -2x + 3x = 1x
-10 + 1x = -7 + -3x + 3x

Combine like terms: -3x + 3x = 0
-10 + 1x = -7 + 0
-10 + 1x = -7

Add '10' to each side of the equation.
-10 + 10 + 1x = -7 + 10

Combine like terms: -10 + 10 = 0
0 + 1x = -7 + 10
1x = -7 + 10

Combine like terms: -7 + 10 = 3
1x = 3

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| [3x+4]=12 | | 4-2d=-2(2d-4) | | .2x-.3=-.7x-2.1 | | 70x-x^2+105=0 | | -13-9x=21-16x | | 6x=45x^2-75 | | 6/5x=2/7 | | 3x^2-4x+21=3x^2+12x+9 | | 3x^2-4x+21=3 | | 6x-18-5x-20=6 | | 6x-18-5x+20=6 | | 90x+10+8x+2=-19 | | (5x-4)(x-7)=(1-4x)(x+1) | | (3x+2)(x+1)=(2x-1)(x+6) | | x^2-4x-12=x^2-3x+2 | | 9x-9=54x+216 | | 45x+225=0 | | 3x+5=7x-35 | | 6x-9=11x+26 | | 6x-4/5=10 | | 3x+5/x-5=7 | | 5x+25=3x+39 | | 5x+25=3x-19 | | 6.9x^2=0 | | 4/3+1=2/3+2n | | x-1/4x=120 | | h=16/9 | | 4p+6r= | | x+x+6+2x=94 | | (4x+4)(5x+6)=0 | | x+5x=2838 | | p^2+5p+2=0 |

Equations solver categories